Female Image in Advertising in The Eva Magazine and Eva.Bg in 2020 – A Comparative Analysis (UNWE Yearbook, 2023)
The objective of the present study is an analysis of gender stereotypes in advertisements in the Eva magazine and eva.bg, in 2020. For this purpose, the content analysis method is used to analyze a systematic random sample of over 500 advertisements, both print and online. Observation is made about the differences between the femlale image in print and in online advertising in the same media.The results indicate that women are generally portrayed in a stereotypical way, supporting the notion that sexism is prevalent in advertisements. Results provide evidence of gender role stereotypes. Portrayal of women varies considerably – from “decorative” female images; through polarizing depictions of women in “dependent” or “non-traditional” roles; to portrayals of women as housewives or equal to men. The comparison of results with those of other researches shows that female image stereotypes in advertising are very similar to the previous ones described by Goffman and Kang. Implications and future research directions are discussed.